THE EFFECTIVENESS OF THE COOPERATIVE LEARNING MODEL TYPE OF STUDENT TEAMS ACHIEVEMENT DIVISION AND THINK PAIR SHARE TOWARD MATHEMATICS LEARNING OUTCOMES - Supeni Supeni; Edi Prajitno (Universitas Ahmad Dahlan, 2019)
The mathematics learning in class VII MTsN 2 Yogyakarta is still centered on a teacher. Students assume that mathematics is a difficult subject resulting in the students' mathematics learning result. The learning by using cooperative learning model types of Student Teams Achievement Division (STAD) and TPS are expected to improve the students' mathematics learning result. This research aims to determine whether there are significant differences between the students' mathematics learning results who are taught using the STAD method and using the Think pair Share(TPS) method, which is better for the students' mathematics learning result, STAD method, or TPS method. This research population is all the students of class VII State Islamic Junior High School (MTsN) 2 Yogyakarta, consisting of seven classes. Meanwhile, the sample in this research there is two classes determined by random sampling. The research sample is class VII B as experiment class A with the STAD method, and class VII D as experiment class B with the Think Pair And Share (TPS) method. This research instrument is a test of mathematics learning results. It is analyzed by using the validity test, distinguishing power, and reliability. Then, data analysis uses t-test two parties and t-test one party. Based on the analysis of the first hypothesis test is t-test two parties on the students' mathematics learning result with significance degree of 5%, and freedom degree of 64 obtained ð‘¡count= 4,0479, and ð‘¡ð‘¡able=1,99894, then ð‘¡count > ð‘¡ð‘¡able so that there is a significant difference between the students' mathematics learning result who are taught by using STAD method and by using TPS method, and the second hypothesis test is t-test one party with significance degree of 5%. Freedom degree of 64 obtained ð‘¡count= 4,0479, and ð‘¡ð‘¡able=1,669525, then ð‘¡count > ð‘¡ð‘¡able so that the STAD method is better than the TPS method of on the students' mathematics learning result.